On the Blowup for the 3D Axisymmetric Incompressible Chemotaxis-Euler Equations. (7th April 2021) - An, Shangyong; Zhang, Qian
Abstract : In this paper, we investigate the 3D incompressible chemotaxis-Euler equations. Taking advantage of the structure of axisymmetric fluids, we establish the blowup criterion of the system using the Fourier localization method.